FENOLOGI PERKEMBANGAN DIAMETER DAN KETINGGIAN BATANG TUMBUHAN PUSPA (Schima wallichii DC. Korth) DI WILAYAH RESORT WONOLELO, TAMAN NASIONAL GUNUNG MERBABU - Ahsan Risfathoni Almadani; Wahyu Gilang Hermawan (Yayasan Nusantara Hasana Berdikari, 2023)
Puspa is one type of plant planted in the conservation area of Mount Merbabu National Park and is quite dominant. In 2021, puspa planting was carried out (Schima wallichii DC. Korth) as many as 2,915 sticks with distribution throughout the conservation area of 14.94 Ha which is precisely located in Sremben Village. Data collection was carried out by a semi-random survey method (purposive random sampling), namely by observation along the location of the PE plant manufacturing area in Wonolelo Resort, Mount Merbabu National Park from the lowest altitude point of Puspa plant planting (Schima wallichii DC. Korth) to the highest altitude point of planting Puspa plants (Schima wallichii DC. Korth). The purpose of this study was to determine the phenology of Puspa plants (Schima wallichii DC. Korth) in the PE plant manufacturing area at Wonolelo Resort, Mount Merbabu National Park at every height.